2014
DOI: 10.1186/1471-2407-14-621
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of argininosuccinate synthetase is associated with cisplatin resistance in hepatocellular carcinoma cell lines: implications for PEGylated arginine deiminase combination therapy

Abstract: BackgroundMany advanced human tumors, including hepatocellular carcinomas (HCC) are auxotrophic for arginine due to down-regulation of argininosuccinate synthetase (ASS1), the rate-limiting enzyme in arginine synthesis. The arginine-lowering agent PEGylated arginine deiminase (ADI-PEG 20) has shown efficacy as a monotherapy in clinical trials for treating arginine-auxotrophic tumors and is currently being evaluated in combination with cisplatin in other cancer types. Epigenetic silencing via methylation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…These results are consistent with previous findings that reduced ASS1 expression is frequently associated with cDDP resistance [6, 13]. Consequently, cDDP-resistant cell lines were more sensitive than their corresponding sensitive counterparts to the killing by ADI-PEG20 (Figure 1B).…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with previous findings that reduced ASS1 expression is frequently associated with cDDP resistance [6, 13]. Consequently, cDDP-resistant cell lines were more sensitive than their corresponding sensitive counterparts to the killing by ADI-PEG20 (Figure 1B).…”
Section: Resultssupporting
confidence: 93%
“…Of note, ADI-PEG20 and Gemcitabine boosted pancreatic cancer growth inhibition by suppressing survivin and blocking NF-κB p65 phosphorylation (serine 536). Similar effects were seen when ADI-PEG20 was combined with the platinum drug Cisplatin to treat malignant melanomas, HCC and ovarian cancer [80,81]. In ASS1-positive HCC cell lines, Cisplatin treatment down-regulated ASS1, rendering those cells sensitive.…”
Section: Strategies To Improve Adi-based Therapymentioning
confidence: 49%
“…Along with others, we have shown that the effectiveness of ADI-PEG20 depends on the levels of ASS expression [17,22,23]. Thus, we assayed ASS expression in a panel of four HCC cell lines, and compared to BJ-1 (normal immortalized fibroblast), A-2058 and Mel1220 which are known to express high, low and absent of ASS expression, respectively [15].…”
Section: Resultsmentioning
confidence: 99%